Recurrent Multicystic Peritoneal Mesothelioma in a Young Male Patient: A Case Report - Eugênio, Guilherme Bernardes Rosa; Müller Filho, Flávio José; Limeira Tenório de Albuquerque, André; Ferrás, Giulia; Antunes, Paulo Eduardo Hernandes (Brazilian Journal of Case Reports, 2026)
Multicystic peritoneal mesothelioma (MPM) is a rare benign neoplasm of mesothelial origin, whose pathogenesis is often associated with chronic inflammatory processes, differing etiologically from malignant mesothelioma due to its lack of association with asbestos exposure. We report the case of a young male patient presenting with chronic, nonspecific abdominal symptoms. Imaging evaluation (CT and MRI) revealed multiple septated cystic lesions consistent with the hypothesis of MPM, demonstrating a molding pattern along adjacent peritoneal surfaces (molding sign), without evidence of parenchymal invasion. Despite surgical resection with no macroscopic residual disease (complete excision), the patient developed local recurrence within 24 months. This report emphasizes that, although histologically benign, MPM exhibits a high rate of biological recurrence, requiring a rigorous long-term radiological surveillance protocol and a multidisciplinary therapeutic approach.